2021
DOI: 10.1097/md.0000000000026788
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of HDACIs in the treatment of metastatic or unresectable renal cell carcinoma with a clear cell phenotype

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Furthermore, HDACi can inhibit tumors by regulating biological activities, such as cell cycle arrest, angiogenesis, immune responses, aging, and apoptosis. Treatment with HDACi has become more effective in recent years ( Singh et al, 2018 ; Chen et al, 2021 ), and has been shown to overcome tyrosine kinase inhibitor resistance induced by B-cell chronic lymphocytic leukemia-lymphoma-like 11 gene ( BIM ) deletion polymorphism in leukemia. The drug corrects the BIM precursor mRNA splicing in chronic myelogenous leukemia cell lines with BIM deletion polymorphisms by reducing the ratio of exon three- and exon 4-containing BIM transcripts, resulting in increased apoptosis ( Rauzan et al, 2017 ; Siegfried and Karni, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HDACi can inhibit tumors by regulating biological activities, such as cell cycle arrest, angiogenesis, immune responses, aging, and apoptosis. Treatment with HDACi has become more effective in recent years ( Singh et al, 2018 ; Chen et al, 2021 ), and has been shown to overcome tyrosine kinase inhibitor resistance induced by B-cell chronic lymphocytic leukemia-lymphoma-like 11 gene ( BIM ) deletion polymorphism in leukemia. The drug corrects the BIM precursor mRNA splicing in chronic myelogenous leukemia cell lines with BIM deletion polymorphisms by reducing the ratio of exon three- and exon 4-containing BIM transcripts, resulting in increased apoptosis ( Rauzan et al, 2017 ; Siegfried and Karni, 2018 ).…”
Section: Discussionmentioning
confidence: 99%